African Youth Engage With Psalms of Lament to Find Their Own Voice of Lament - Dickie, June F. (ournal of Theology for Southern Africa, 2018)
The biblical psalms of personal lament show certain characteristics which can assist African youth struggling with various issues to voice their own laments. In this empirical study, "pain-bearers" from various sectors in South Africa (refugees, AIDS-sufferers, and members of the LGBT community) participated in short workshops where they studied Psalms 3 and 13. They then composed their own laments using features of biblical lament: complaints, petitions, requests for justice, and an honest expression of their mood (often oscillating between negative and positive statements). Analysis of the lament compositions shows they include the elements considered essential by trauma-therapists (establishing safety, reconstructing the trauma-story, and restoring connections with one's community), and lament-researchers (restoring the voice of a subject, providing a sense of justice, and connecting with God), and could result in biological healing, a possible application of the work of neuro-researchers. Thus one can posit that the expression of lament could promote wholeness for sufferers.
free